2019
DOI: 10.1080/14461242.2019.1604150
|View full text |Cite
|
Sign up to set email alerts
|

Fat acceptance 101: Midwestern American women’s perspective on cultural body acceptance

Abstract: Weight stigma is pervasive in the US, with body size being pathologised and weight loss urged for those of higher weights. However, there is a growing movement for fat acceptance and body positivity. The present study explored perceptions and experiences of cultural body acceptance trends among Midwestern American women who are trying to, or have tried to, "accept" their bodies. Participants (n=18) are self-identified women who have ever been labelled 'obese' on the Body Mass Index and have ever tried to devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
0
11
0
1
Order By: Relevance
“…Finally, as the body positivity movement gains momentum, Sastre (2014) performed a discourse analysis of various body positive websites to interrogate the ways in which these sites facilitate an enactment of body positive tenants. While each study acknowledged the contribution body positive spaces had made in the way of increased representation and access, the movement was characterized as 'lip service' with increased skepticism; citing the escalating "institutionalized, corporatized, and social media pushes for greater diversity" (Bombak et al, 2019). Participants were suspicious of advocates' ultimate motivations as countercultural resistance to conformity successfully and productively merged with entrepreneurial culture.…”
Section: Consumer Activismmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, as the body positivity movement gains momentum, Sastre (2014) performed a discourse analysis of various body positive websites to interrogate the ways in which these sites facilitate an enactment of body positive tenants. While each study acknowledged the contribution body positive spaces had made in the way of increased representation and access, the movement was characterized as 'lip service' with increased skepticism; citing the escalating "institutionalized, corporatized, and social media pushes for greater diversity" (Bombak et al, 2019). Participants were suspicious of advocates' ultimate motivations as countercultural resistance to conformity successfully and productively merged with entrepreneurial culture.…”
Section: Consumer Activismmentioning
confidence: 99%
“…While this discourse of failed citizenship is a demonstrated characteristic of anti-fat discourse found in both traditional (Cain et al, 2017) and new media (Webb et al, 2019), body positivity was also found to engage in neoliberal ideology despite its commitment to resisting the same systems that had marginalized them. Minor turns in this literature are reflected in fatshion and beauty (Gurrieri & Cherrier, 2013;Scaraboto & Fischer, 2013), health and fitness (Webb et al, 2017;Webb et al, 2019) and self-care (Bombak, Meadows, & Billette, 2019;Cain et al, 2017).…”
Section: Neoliberal Construction Of Fatnessmentioning
confidence: 99%
See 3 more Smart Citations